Investment-cash flow sensitivities, credit rationing and financing constraints - Leonardo Becchetti; Annalisa Castelli; Iftekhar Hasan (Bank of Finland, 2008)
The controversy over whether investment-cash flow sensitivity is a good indicator of financing constraints is still unresolved. We tackle it from several different angles and cross-validate our analysis with both balance sheet and qualitative data on self-declared credit rationing and financing constraints. Our qualitative information shows that (self-declared) credit rationing is (weakly) related to both traditional a priori factors such as firm size, age and location and lenders rational decisions based on their credit risk models. We use our qualitative information on firms that were denied credit to provide evidence relevant to the investment-cash flow sensitivity debate. Our results show that self-declared credit rationing significantly discriminates between firms that do and do not have such sensitivity, whereas a priori criteria do not. The same result does not apply when we consider the wider group of financially constrained firms (which do not seem to have a higher investment-cash flow sensitivity), which supports the more recent empirical evidence in this direction.
URN:NBN:fi:bof-20140807398
Keywords: 330